A sensitivity-based procedure to select representative fish species for the Marine Strategy Framework Directive indicator development, applied to the Greater North Sea - Victoria Sarrazin (Elsevier, 2021)
Harmonizing biodiversity assessments under the Marine Strategy Framework Directive (MSFD) at the pan-European level is a crucial task for the Regional Sea Conventions and EU Member States in the coming years, particularly for fish assessment in Descriptor 1 (biodiversity). Precondition for coherent fish assessments is the establishment of a regionally coordinated set of species for each species group. This study presents an objective approach to select fish species while implementing the scientific requirements and standards given by the Commission Decision (EU) 2017/848. The method was applied to the OSPAR Region Greater North Sea (GNS) for the species groups coastal fishes, demersal shelf fishes and pelagic shelf fishes. We first assessed the representativeness of species by considering their distributional extent from survey data and literature. Second, we calculated sensitivity and threat scores for each of the representative species based on life-history traits and current conservation schemes. Third, we analysed the fish composition structure using cluster analyses for a number of functional traits. Species were finally selected from all functional groupings with priority for sensitive and threatened species. For the GNS this resulted in 15 coastal, 34 demersal shelf and 7 pelagic shelf species being selected. This study demonstrates that the requirements of the EU are implementable in an objective way. This approach, which is also transferable to other marine regions, could serve as a neutral foundation for the crucially needed coordination process among Member States demanded by the Commission Decision (EU) 2017/848 and contribute to significantly progressing to assess fish in Descriptor 1, in the context of the MSFD.